Learning from preventable deaths: exploring case record reviewers' narratives using change analysis. (September 2014) - Hogan, Helen; Healey, Frances; Neale, Graham; Thomson, Richard; Black, Nick; Vincent, Charles
Objective: To determine if applying change analysis to the narrative reports made by reviewers of hospital deaths increases the utility of this information in the systematic analysis of patient harm. Design: Qualitative analysis of causes and contributory factors underlying patient harm in 52 case narratives linked to preventable deaths derived from a retrospective case record review of 1000 deaths in acute National Health Service Trusts in 2009. Participants: 52 preventable hospital deaths. Setting: England. Main outcome measures: The nature of problems in care and contributory factors underlying avoidable deaths in hospital. Results: The change analysis approach enabled explicit characterisation of multiple problems in care, both across the admission and also at the boundary between primary and secondary care, and illuminated how these problems accumulate to cause harm. It demonstrated links between problems and underlying contributory factors and highlighted other threats to quality of care such as standards of end of life management. The method was straightforward to apply to multiple records and achieved good inter-rater reliability. Conclusion: Analysis of case narratives using change analysis provided a richer picture of healthcare-related harm than the traditional approach, unpacking the nature of the problems, particularly by delineating omissions from acts of commission, thus facilitating more tailored responses to patient harm.